Creating Database-Backed Library Web Pages : Using Open Source Tools. - Westman, Stephen R. (ALA Editions, 2006)
Database-backed Web pages provide many advantages for libraries: users get accurate and up-to-date information in real time, and site maintenance and data publishing are much easier. As appealing an idea as database-backed pages are, the "how-tos" of creating them remain a mystery to many librarians. This hands-on resource provides the tools to improve users' results by providing current data, make site maintenance and data publishing much easier, and even add new usefulness to existing data. Following these clear, step-by-step explanations, readers will find proven solutions for answers to qu.